2008
DOI: 10.1016/j.schres.2008.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in symptoms, functioning and social support in patients at ultra-high risk for developing a psychotic disorder

Abstract: Gender differences have been widely observed in the clinical presentation, psychosocial functioning and course of illness in first episode and chronic patients suffering from schizophrenia. However, little is known about gender differences in the psychosis prodrome. This study investigated gender differences in symptoms, functioning and social support in individuals at ultra-high-risk for developing a psychotic disorder. Sixty-eight ultra-high-risk patients were assessed at baseline, and twenty-seven returned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
61
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 35 publications
10
61
1
Order By: Relevance
“…Another smaller, recent CHR study also demonstrated more negative symptoms among high-risk males than females (Corcoran et al, 2011). These findings replicate and extend earlier retrospective findings from smaller high-risk and prodromal studies (Willhite et al, 2008). …”
Section: Introductionsupporting
confidence: 89%
“…Another smaller, recent CHR study also demonstrated more negative symptoms among high-risk males than females (Corcoran et al, 2011). These findings replicate and extend earlier retrospective findings from smaller high-risk and prodromal studies (Willhite et al, 2008). …”
Section: Introductionsupporting
confidence: 89%
“…However, despite comparatively better social and role function, the females were still at appreciable risk for psychosis, as two of the twelve (17%) developed psychosis. Of note, a general pattern of superior functioning in females has been described across early stages of schizophrenia – in other CHR cohorts 1213 and among first episode psychosis patients 14 .…”
Section: Discussionmentioning
confidence: 80%
“…Several investigations support the fact that there are gender differences in age of onset, severity of symptoms and long-term functioning in schizophrenia, with different patterns of prodromal symptoms beginning before the disorder onset [29,30]. As Lewine [31] has already indicated, several aspects of schizophrenia, such as the onset, may be best pursued from a biological (sex difference) perspective, whereas a sociocultural perspective, including gender differences, may be better to understand different aspects, such as neuropsychological functioning.…”
Section: Schizophreniamentioning
confidence: 96%